Discovery and mechanistic study of a photocatalytic indoline dehydrogenation for the synthesis of elbasvir. Issue 3 (5th January 2016) - Yayla, Hatice G.; Peng, Feng; Mangion, Ian K.; McLaughlin, Mark; Campeau, Louis-Charles; Davies, Ian W.; DiRocco, Daniel A.; Knowles, Robert R.
Abstract : Elbasvir is a potent NS5A antagonist for the treatment of chronic hepatitis C. Abstract : Elbasvir is a potent NS5A antagonist for the treatment of chronic hepatitis C. A seemingly trivial indoline oxidation en route to the target compound was complicated by epimerization of a stereogenic hemiaminal center under most standard oxidation conditions. To address this issue, a novel visible light photoredox process for indoline oxidation was developed involving an iridium photosensitizer and environmentally-benign perester oxidant. The reaction was discovered through a high-throughput experimentation campaign and the optimized process was demonstrated on 100 g scale in flow to afford a key intermediate towards the target compound. A battery of kinetic, electrochemical, and spectroscopic studies of this process indicates a radical chain mechanism of dehydrogenation involving selective HAT from the substrate by an alkoxy radicals. Notably, isotope effects were used to validate the chain mechanism when quantum yield data proved ambiguous.